PEMENUHAN ASAS KEPASTIAN HUKUM DALAM PERATURAN OTORITAS JASA KEUANGAN TENTANG EQUITY CROWDFUNDING - Luthfy, Riza Multazam (Fakultas Hukum Universitas Langlangbuana, 2024)
The issuance of POJK RI. No. 37/POJK.04/2018 is one of the efforts of the OJK in responding to the development of equity crowdfunding in Indonesia. This regulation basically requires legal certainty, so as to provide security and comfort for every citizen in running the fintech industry. In an effort to assess the fulfillment of the principle of legal certainty in the RI POJK. No. 37/POJK.04/2018, the author uses the theory of legal certainty according to Gustav Radbruch's theory. The preparation of this article uses a philosophical approach and a statutory approach. The author concludes that the principle of legal certainty has been fulfilled in the POJK RI. No. 37/POJK.04/2018, because it has been stated through its philosophical basis and norms. This is in accordance with what has been stated by Gustav Radbruch, where in addition to justice and expediency, the provisions outlined through laws and regulations must be able to provide legal certainty for every citizen.